The Influence of Motivation, Social Media, and the Social Environment on Interest in Entrepreneurship - Amiruddin Husain (Jurnal Economic Resource, 2022)
The purpose of this study was to determine the effect of the relationship between social media motivation and the social environment on interest in entrepreneurship. Data was obtained by distributing questionnaires to respondents, namely students of the Faculty of Economics and Business, Muslim University of Indonesia, with a total of 83 respondents. Data analysis used linear regression analysis. Data processing is done using the IBM SPSS 24 program. The results showed that motivation had a negative and significant effect on interest in entrepreneurship, social media had a positive and significant effect on interest in entrepreneurship, and the social environment had a positive and significant effect on entrepreneurial interest in students of the Faculty of Economics and Business, Universitas Muslim Indonesia.